2021
DOI: 10.1002/hed.26822
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of patient stratification in human papilloma virus‐associated oropharyngeal squamous cell carcinoma by defining a multivariable risk score

Abstract: Background: Precise risk stratification models are necessary to determine patient selection for deintensifying treatment trials in human papilloma virus (HPV)-associated oropharyngeal squamous cell cancer (HPV+ OPSCC).Methods: We examined 526 cases with OPSCC treated at our department between 2002 and 2017. Every patient was classified after the 7th and 8th edition UICC staging manual. For HPV+ OPSCC, we calculated a simple risk score with four risk groups based on multivariable Cox regression analysis of clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A continuous, diffuse staining for p16 within the cancer area of the tissue sections was considered positive, while a focal staining or no staining were considered negative. The cut-off of p16 positivity was considered a diffuse staining corresponding to 70% of p16 positive tumor cells [13]. IHC slides were evaluated by one pathologist blinded to any other clinical information or HPV DNA or RNA status.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A continuous, diffuse staining for p16 within the cancer area of the tissue sections was considered positive, while a focal staining or no staining were considered negative. The cut-off of p16 positivity was considered a diffuse staining corresponding to 70% of p16 positive tumor cells [13]. IHC slides were evaluated by one pathologist blinded to any other clinical information or HPV DNA or RNA status.…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggest that these factors could be used for a better stratification and management of this category of patients [35]. A research team from Lyon used p16/p53 algorithm to predict HPV tumor status in OPSCC, and authors from Germany concluded that tobacco, alcohol abuse, age, and gender should be added to the current UICC (The Union for International Cancer Control) staging system to improve the risk stratification in HPV+ OPSCC [13,36]. Korsten LHA et al from Amsterdam evaluated the health-related quality of life for HPV-positive OPSCC patients.…”
Section: Opscc Hpv Dna Positive P16 Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are various radiographic biomarkers for HNSC patient outcome, namely using PET-CT scans rather than clinical evaluation and CT alone (107)(108)(109)(110) and tumor volume (110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121). However, knowledge of HPV status alone is also a prognostic biomarker for HNSC in its own right, indicating better survival compared to HPV(-) (122) Unfortunately, a subset of HPV(+) individuals do not display improved survival (11,13,(123)(124)(125)(126)(127)(128), and therefore, a need exists for criterion to further stratify this subset of HPV(+) patients for guiding treatment decisions. HPV(+) tumors have increased tumor immune infiltrates, which have also been shown to be positive for prognosis (57,68,(129)(130)(131).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol and nicotine consumption are known risk factors for the development of HNSCC and the human papilloma virus (HPV) is an established risk factor for OPSCC 2,3 . HPV‐positive OPSCC cases are characterized by a superior response to therapies and longer survival 4,5 . However, overall, the 5‐year survival rate for OPSCC and LSCC is still low and additional risk factors seem to play a crucial role in carcinogenesis and tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%